Transplacement mutagenesis: a novel in situ mutagenesis system using phage-plasmid recombination. - Unger, M W (1999)
Site-specific mutagenesis provides the ability to alter DNA with precision so that the function of any given gene can be more fully understood. Several methods of in vitro mutagenesis are time-consuming and imprecise, requiring the subcloning and sequencing of products. Here we describe a rapid, high fidelity method of in situ mutagenesis in bacteriophage lambda using transplacement. Using this method, mutations are transferred from oligonucleotides to target phages using a plasmid interface. A small (50 bp) homology region bearing a centred point mutation is generated from oligonucleotides and subcloned into a transplacement plasmid bearing positive and negative phage selectable markers. Following a positive/negative selection cycle of integrative recombination and excision, the point mutation is transferred precisely from plasmid to phage in a subset ( approximately 25-50%) of recombinants. As the fidelity of both oligonucleotide synthesis and phage-plasmid recombination is great, this approach is extremely reliable. Using transplacement, point mutations can be accurately deposited within large phage clones and we demonstrate the utility of this technique in the construction of gene targeting vectors in bacteriophages.